Perspective: Evolution of Control Variables and Policies for Closed-Loop Deep Brain Stimulation for Parkinson’s Disease Using Bidirectional Deep-Brain-Computer Interfaces - Bronte-Stewart, Helen M.; Petrucci, Matthew N.; O’Day, Johanna J.; Afzal, Muhammad Furqan; Parker, Jordan E.; Kehnemouyi, Yasmine M.; Wilkins, Kevin B.; Orthlieb, Gerrit C.; Hoffman, Shannon L. (Frontiers in Human Neuroscience, 2020)
A deep brain stimulation system capable of closed loop neuromodulation is a type of bidirectional deep brain computer interface (dBCI), in which neural signals are recorded, decoded and then used as the input commands for neuromodulation at the same site in the brain. The challenge in assuring successful implementation of bidirectional dBCIs in Parkinson’s disease (PD) is to discover and decode stable, robust and reliable neural inputs that can be tracked during stimulation, and to optimize neurostimulation patterns and parameters (control policies) for motor behaviors at the brain interface, which are customized to the individual. In this perspective, we will outline the work done in our lab regarding the evolution of the discovery of neural and behavioral control variables relevant to PD, the development of a novel personalized dual threshold control policy relevant to the individual’s therapeutic window and the application of these to investigations of closed loop STN DBS driven by neural or kinematic inputs, using the first generation of bidirectional dBCIs.